Novel Immunity Proteins Associated with Colicin M-like Bacteriocins Exhibit Promiscuous Protection in Pseudomonas - Ghequire, Maarten G. K.; Kemland, Lieselore; De Mot, René (Frontiers in Microbiology, 2017)
Bacteriocins related to colicin M, acting via cleavage of the cell wall precursor lipid II, have been characterized in γ- and β-proteobacteria. Depending on the species, immunity is provided by either an inner membrane-anchored periplasmic protein or by an integral membrane protein. In Pseudomonas however, the immunity partner of colicin M-like bacteriocins remains unknown. Based on an in silico analysis in pseudomonads genomes, we here identify a gene encoding a putative immunity partner that represents a novel type of integral membrane protein (PmiA, Pseudomonas colicin M-like immunity type A). By heterologous expression of pmiA genes in susceptible strains, we show that immunity to colicin M-like bacteriocins is indeed provided by the cognate PmiA. Sequence homology among PmiA proteins is essentially absent, except for a short motif with a conserved periplasm-exposed aspartate residue. However, PmiA’s protective function is not abolished by changing this acidic residue to the uncharged alanine. Immunity by PmiAs appears promiscuous to the extent that PmiA homologues from a clade sharing less than 40% pairwise amino acid identity, equally provide protection against the bacteriocin linked to the original PmiA. This study shows that multiple immunity factors have evolved independently to silence lipid II-targeting enzymatic bacteriocins. Their relaxed bacteriocin immunization capacity contrasts to the strict specificity of immunity proteins shielding the enzymatic domain of nuclease bacteriocins. The nature of associated immune functions needs consideration when using such natural protein antibiotics or designing novel variants.